Effects of melatonin on the synthesis of estradiol and gene expression in pig granulosa cells. Issue 2 (31st January 2019) - Liu, Ying; Yang, Yalan; Li, Wentong; Ao, Hong; Zhang, Yanmin; Zhou, Rong; Li, Kui
Abstract: The interaction of granulosa cells (GCs) with oocytes is important to regulate follicle development. The exogenous melatonin promoting the maturation of oocytes by GCs has been approved in pig, however, the transcriptome profile and the functions of the genes regulated by melatonin in GCs have not yet to be fully characterized. In this study, we found melatonin could stimulate the synthesis of estradiol in pig GCs. The RNA‐seq was used to explore the effects of melatonin on gene expression, a total of 89 differentially expressed genes (DEGs) were identified. Gene ontology analysis showed DEGs which associated with regulation of cell proliferation, cell cycle, and anti‐apoptosis were significantly enriched. The functions of two DEGs, NOTCH2 and FILIP1L, were studied in pig GCs. The results showed that NOTCH2 inhibited the synthesis of estradiol, but FILIP1L promoted the synthesis of estradiol. Furthermore, inhibiting NOTCH2 in granulosa cells cocultured with cumulus‐oocyte‐complexes had no obvious effect on the maturation of pig oocyte, but could upregulate the cleavage rate of oocyte. We proved that FILIP1L had no effect on the maturation and cleavage of pig oocytes. Our work deepens the understanding of melatonin's effects on GCs and oocyte. The DEGs we found will be beneficial to reveal mechanisms of melatonin acting on GCs and oocytes and design the pharmacological interventions.